Concomitant lithium increases radioiodine uptake and absorbed doses per administered activity in graves’ disease: comparison of conventional versus lithium-augmented radioiodine therapy - Khreish, Fadi; Schaefer-Schuler, Andrea; Roth, Leonie; Burgard, Caroline; Rosar, Florian; Ezziddin, Samer (Frontiers in Medicine, 2024)
Background: Lithium inhibits iodine and thyroid hormone release from thyroid cells, possibly increasing radioiodine retention and anti-hyperthyroid efficacy when given adjunctively to radioiodine therapy of Graves' disease. However, literature contains limited dosimetric data regarding the influence of concomitant lithium in this setting. Methods:We retrospectively compared dosimetric variables in patients undergoing RAI with/without adjunctive lithium (n=52 each). We assessed two low-dose, shortduration oral lithium carbonate regimens, 450 mg/d (n=22) or 900 mg/d (n=30), for a mean 4.7 ± 1.4 d starting upon RAI administration. Patients underwent diagnostic testing to measure thyroidal radioiodine uptake (RAIU) 24 h ± 2 h after ingesting up to 5 MBq radioiodine, receiving individualized RAI activities 24 h later. Using ≥3 RAIU daily measurements starting 24 h post-RAI, effective radioiodine half-life and absorbed dose to the thyroid were determined; we also calculated the absorbed dose per administered activity. Rates of GD cure, defined as reaching euthyroidism or hypothyroidism post-RAI, were evaluated in patients with ~6 months or longer post-RAI.Results: The lithium dosage subgroups had similar dosimetric values, and thus are considered together. Lithium patients and controls had similar average "diagnostic" RAIU (51.1% ± 15.7% vs. 50.6% ± 13.8%, p=0.820), but the former had significantly higher RAIU post-RAI (56.3% ± 13.5% vs. 49.1% ± 13.5%, p=0.002), reflecting significantly greater change in the former (+16.2% ± 30.4% vs. -1.8% ± 16.1%, p=0.001). Radioiodine effective half-life was non-significantly longer in lithium patients (5.43 ± 1.50 d vs. 5.08 ± 1.16 d, p = 0.192). The mean RAI administered activity was 27% less in lithium patients (677 ± 294 MBq vs 930 ± 433 MBq, p=0.001), but GD cure rates were similar (83% vs. 82%, p=0.954), possibly due to the significantly higher thyroid dose in the lithium patients, especially in thyroid gland with a volume ≤20 ml (1.04 ± 0.44 Gy/MBq vs. 0.76 ± 0.30 Gy/MBq, p=0.020). Day 3 serum lithium concentrations were low, no lithium toxicity was noted. Conclusion: Lithium augmentation may increase the RAIU and thyroid absorbed dose and therefore may permit potentially decreased RAI activities without sacrificing efficacy. Our observations should be confirmed in a prospective, randomized trial.